Treatment of long oblique femoral fracture in a Rhesus macaque monkey - hamidreza fattahian; hamid mohiedin; rouzbeh moridpour; fereshte Khomejani Farahani; mahya Jazini Dorche; soude Ansari (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2015)
A seven months old Rhesus macaque monkey weighing 1.800 kg was referred to a private small animal clinic with pain and non-weight bearing lameness of right leg. Anamnesis and clinical examination revealed the presence of trauma in right femoral region. In radiologic evaluation using Medio lateral and ventrodorsal views, femoral long oblique fracture was diagnosed. Based on clinical examination and diagnostic imaging findings, surgical treatment was suggested. Femoral shaft fracture is a common type of fracture and internal fixation with intramedullary pins and cerclage wire are performed in these type of fractures.